2011
DOI: 10.5812/aapm.1782
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the Pressor Response to Tracheal Intubation in Severe Preeclampsia: Relative Efficacies of Nitroglycerine Infusion, Sublingual Nifedipine, and Intravenous Hydralazine

Abstract: A B S T R A C T Background:The pressor response to laryngoscopy is known to be exaggerated in patients with severe preeclampsia. Objectives: The aim of the present study was to compare the efficacies of continuous intravenous (IV) infusion of nitroglycerine, IV hydralazine, or sublingual nifedipine in modifying cardiovascular responses to endotracheal intubation, in women with severe preeclampsia undergoing cesarean delivery under general anesthesia. Patients and Methods: A total of 120 patients undergoing ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Opioids was also used in epidural space in pregnant women for cesarean section without significant difference in maternal complications and Apgar scores (21). Safavi M et al showed that some drugs such as Nitroglycerin are effective in attenuating the pressor response to tracheal intubation in severe preeclampsia and could be used instead of opioids to control hemodynamic responses (22). Remifentanil and fentanyl were also used effectively in endotracheal intubation without use of neuromuscular blocking drugs (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…Opioids was also used in epidural space in pregnant women for cesarean section without significant difference in maternal complications and Apgar scores (21). Safavi M et al showed that some drugs such as Nitroglycerin are effective in attenuating the pressor response to tracheal intubation in severe preeclampsia and could be used instead of opioids to control hemodynamic responses (22). Remifentanil and fentanyl were also used effectively in endotracheal intubation without use of neuromuscular blocking drugs (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…Laryngoscopy, known as an invasive procedure in the anesthesia process, that by sympathetic nervous system stimulation causes an increase in the release of catecholamines and increase in blood pressure and heart rate, and arrhythmia, which can have dangerous consequences in patients with a history of cardiovascular diseases (1)(2)(3). A safe anesthesia for the patient and less stress for anesthesiologists is obtained due to interventions to reduce anesthesia complications.…”
Section: Introductionmentioning
confidence: 99%
“…This sympathetic stimulation results in tachycardia and elevation of blood pressure. [1][2][3][4][5][6][7] Thus different drugs such as local anesthetics, opioids, calcium channel blockers, short acting β-adrenergic blockers, and their combinations have been used to prevent this hemodynamic responses but none was found to be most effective. [8][9][10][11][12][13][14] Fentanyl, a commonly used opioid along with hypnotic agents have been used to diminish hemodynamic responses to tracheal intubation.…”
Section: Introductionmentioning
confidence: 99%